-2P+1⋅4+1.5⋅(-2)=0

Simplify each term.

Multiply 4 by 1.

-2P+4+1.5⋅(-2)=0

Multiply 1.5 by -2.

-2P+4-3=0

-2P+4-3=0

Subtract 3 from 4.

-2P+1=0

-2P+1=0

Subtract 1 from both sides of the equation.

-2P=-1

Divide each term in -2P=-1 by -2.

-2P-2=-1-2

Cancel the common factor of -2.

Cancel the common factor.

-2P-2=-1-2

Divide P by 1.

P=-1-2

P=-1-2

Cancel the common factor of -1 and -2.

Rewrite -1 as -1(1).

P=-1(1)-2

Cancel the common factors.

Rewrite -2 as -1(2).

P=-1⋅1-1⋅2

Cancel the common factor.

P=-1⋅1-1⋅2

Rewrite the expression.

P=12

P=12

P=12

P=12

The result can be shown in multiple forms.

Exact Form:

P=12

Decimal Form:

P=0.5

Solve for P -2P+1*4+1.5*(-2)=0